2015
DOI: 10.1158/2326-6066.cir-14-0207
|View full text |Cite
|
Sign up to set email alerts
|

Impact of NRAS Mutations for Patients with Advanced Melanoma Treated with Immune Therapies

Abstract: Activating NRAS mutations are found in 15-20% of melanomas. Immune therapies have become a mainstay in advanced melanoma treatment. We sought to evaluate whether tumor genotype (e.g. NRAS mutations) correlate with benefit from immune therapy in melanoma. We identified 229 melanoma patients treated with immune therapies (interleukin-2, ipilimumab, or anti-programmed cell-death-1/ligand-1 (PD-1/PD-L1)) at three centers, and compared clinical outcomes following immune therapy for patients with or without NRAS mut… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
139
3
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 155 publications
(156 citation statements)
references
References 36 publications
10
139
3
1
Order By: Relevance
“…Activating NRAS mutations, which are found in 15-20% of melanomas, have also been studied in 229 patients with melanoma treated with immune therapies (IL-2, ipilimumab, anti-PD-1 therapy, and anti-PD-L1 therapy) (105). Clinical outcomes were superior in the NRAS- mutant cohort than other cohorts, as demonstrated by improved response to first-line immune therapy, response to any line of immune therapy, clinical benefit, and progression-free survival.…”
Section: Future Directionsmentioning
confidence: 99%
“…Activating NRAS mutations, which are found in 15-20% of melanomas, have also been studied in 229 patients with melanoma treated with immune therapies (IL-2, ipilimumab, anti-PD-1 therapy, and anti-PD-L1 therapy) (105). Clinical outcomes were superior in the NRAS- mutant cohort than other cohorts, as demonstrated by improved response to first-line immune therapy, response to any line of immune therapy, clinical benefit, and progression-free survival.…”
Section: Future Directionsmentioning
confidence: 99%
“…The ability to identify the subset of long-term survivors could have an important impact on treatment options, including first-line as well as salvage therapy. Previously a series of studies have examined somatic alterations to identify possible predictive signatures; these have included studies of gene expression signature associated with immune infiltration (14), neoantigen load (1517), NRAS mutation status (18) and neoantigen-derived tetrapeptide signature (15). Of these, the neoantigen load is most promising, particularly for treatment of melanoma (15,16) and NSCLC (17).…”
Section: Introductionmentioning
confidence: 99%
“…24 Relating to immunotherapy, it has recently been shown that harboring an NRAS mutation increases the response rate (RR) to checkpoint inhibitors with no significant impact on OS and progression-free survival (PFS). 28,29 A recent retrospective study affirmed this assumption: although mutational status had no influence on OS in anti-CTLA-4 treated patients, a non-statisticallysignificant trend for superior clinical outcome in NRAS mutant patients was observed. 30 As outlined previously, the third most commonly reported mutation is the inactivating mutation of NF1, which shows similar OS compared to BRAF-mutant, NRASmutant or triple wt melanomas.…”
Section: Driver Mutations As Prognostic Factors In Melanoma?mentioning
confidence: 97%